1972
DOI: 10.1038/bjc.1972.9
|View full text |Cite
|
Sign up to set email alerts
|

Thymectomy and Cancer—A Follow-Up Study

Abstract: Three hundred and eighty-two patients undergoing thymectomy for myasthenia gravis at 4 London hospitals during the years 1942-64 have been followed to the end of 1967. Five of these patients died from extrathymic tumours while 5·5 would have been expected to do so from the national experience. An additional 5 patients developed non-fatal extrathymic tumours during the period of follow-up. These data provide no evidence that adult thymectomy is followed by an increased risk of neoplastic disease, but more prolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
1

Year Published

1972
1972
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 19 publications
3
11
1
Order By: Relevance
“…10 There also were a few studies that specifically addressed the association between myasthenia gravis and extrathymic malignancy, in which the incidence of malignancies ranged from 5% to 18% in patients with myasthenic thymoma. [11][12][13][14][15][16] The results of the latter studies cannot be compared with our current results, because patients with nonmyasthenic thymoma were excluded. The variation in the numbers and tumor types may have resulted in part from the different nature or referral patterns of the institutions and the length of follow-up.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…10 There also were a few studies that specifically addressed the association between myasthenia gravis and extrathymic malignancy, in which the incidence of malignancies ranged from 5% to 18% in patients with myasthenic thymoma. [11][12][13][14][15][16] The results of the latter studies cannot be compared with our current results, because patients with nonmyasthenic thymoma were excluded. The variation in the numbers and tumor types may have resulted in part from the different nature or referral patterns of the institutions and the length of follow-up.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies also disclosed that resection of thymus by itself did not enhance the emergence of extrathymic tumors. [11][12][13][14][15][16] Some authors even suggested that thymectomy reduced the incidence of extrathymic neoplasms in myasthenic patients. 11,13,14 Whether the elevated risk of second malignancies in thymoma patients results from an impaired or disordered immunologic function requires more subtle research.…”
Section: Discussionmentioning
confidence: 99%
“…It is not unexpected that there is an increase of other cancers with thymoma because the role of thymus in immune function is well documented. Children born athymic have severe T-cell and variable B-cell deficiencies [14]. Although it is less well described in adults, early experiments did show a change in the immune system of adult rats after thymectomy [ 141, This information combined with the fact that immunosuppressed patients, such as transplant patients, have a higher chance of developing malignancies [ 181 leads us to believe that the thymus may indeed play some role in immunosurveillance to prevent the development of malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…The investigation was prompted by interest in the concept of "immunological surveillance" and by experimental evidence suggesting the likely importance of the thymus in any natural immunological defence mechanisms against cancer. A preliminary report concerned the findings in 383 British patients who underwent thymectomy during the years and who had been successfully followed to the end of 1967 (Vessey & Doll, 1972 The number of years that these patients have been at risk of dying have been computed separately for those with and without thymoma, for each sex and 5-year age group, for each 5-year period after thymectomy (0-4, 5-9, etc.) and for each 5-year calendar period of observation (1940-44.…”
mentioning
confidence: 99%